Plasmonic‐Functionalized Broadband Perovskite Photodetector. Issue 8 (14th February 2018) - Du, Bowen; Yang, Wenqiang; Jiang, Qiao; Shan, Hangyong; Luo, Deying; Li, Bowen; Tang, Weichen; Lin, Feng; Shen, Bo; Gong, Qihuang; Zhu, Xing; Zhu, Rui; et al.
Abstract: Organic–inorganic hybrid perovskite photodetectors have been reported to possess superior optoelectronic properties, such as high sensitivity, ultrafast response, and capability of strongly absorbing the light in the visible range. While in the near‐infrared range, the performances of these photodetectors deteriorate seriously, originating from the weak coupling of infrared light to the perovskites. In this study, an organic–inorganic hybrid perovskite photodetector on arrays of Au nanostructures is fabricated, which exhibits a remarkable photocurrent enhancement in the visible and near‐infrared range, ascribed to the huge localized electric field induced by the surface plasmon resonance of Au nanostructures. The maximum external quantum efficiency of this photodetector is as high as about 65%, 2.5 times that on a usual Si/SiO2 substrate without Au nanostructures. Obviously, by exploiting Au nanostructures, the light harvesting ability of the photodetector breaks through the perovskite absorption edge, and extends to the near‐infrared range. Abstract : A broadband perovskite photodetector, based on plasmonic‐functionalized multilayer substrate, displays an extended response spectrum beyond the ordinary visible‐light into the near‐infrared region. By using the enhanced localized electrical field from the plasmonic substrate, this device shows improved external quantum efficiency, low dark current, and high specific detectivity at zero bias.